2017
DOI: 10.1111/apt.14424
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of atrophic gastritis and intestinal metaplasia after Helicobacter pylori eradication ‐ a prospective study for up to 10 years

Abstract: H. pylori eradication may be a preventative strategy for intestinal-type gastric cancer by regression of atrophic gastritis and intestinal metaplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 71 publications
7
123
2
3
Order By: Relevance
“…Along with greater extent and higher degree of gastric mucosal atrophy, and also with the variation in biological characteristics, the risk of developing stomach cancer will increase gradually. Recently several studies have showed premalignant conditions including AG and IM may be regressed by appropriate interventional treatment before it reaches “point of no return”,35, 36 which can reduce the incidence of GC. Therefore, precise evaluation focusing on severity and biological behaviors and proper intervention of high‐risk AG patients is of great significance for the prevention of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Along with greater extent and higher degree of gastric mucosal atrophy, and also with the variation in biological characteristics, the risk of developing stomach cancer will increase gradually. Recently several studies have showed premalignant conditions including AG and IM may be regressed by appropriate interventional treatment before it reaches “point of no return”,35, 36 which can reduce the incidence of GC. Therefore, precise evaluation focusing on severity and biological behaviors and proper intervention of high‐risk AG patients is of great significance for the prevention of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…26 Six biopsy specimens were obtained from the lesser curvature, and four specimens were obtained from the greater curvature, evenly from the mid antrum and mid corpus, regardless of cancer status ( Figure S1). At each EGD, the biopsy specimens were taken to confirm diagnosis of GC and up to ten biopsy specimens were additionally obtained for H. pylori testing and histological examination.…”
Section: Esophagogastroduodenoscopy Helicobacter Pylori Tests Andmentioning
confidence: 99%
“…Grades of IM did not improve after ≥ 3 years of eradication in comparison with grades of IM of the HP‐negative group (Fig. b) . However, AG in both the antrum and corpus improved more quickly up to grade 0 than IM in both antrum and corpus in the present study (Fig.…”
Section: Introductionmentioning
confidence: 43%
“…pylori ‐eradicated [ n = 442]) with long‐term follow‐up for up to 10 years, we showed that AG and IM in both the antrum and the corpus continuously improved after HP eradication until reaching a point that they were not significantly different compared with those in the HP‐negative group (Fig. ) . The speed or degree of reversibility was found to be different between AG and IM (Fig.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation